2016
DOI: 10.1155/2016/6909745
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Hydrodynamics for Bionic Oscillating Hydrofoil Based on Panel Method

Abstract: The kinematics model based on the Slender-Body theory is proposed from the bionic movement of real fish. The Panel method is applied to the hydrodynamic performance analysis innovatively, with the Gauss-Seidel method to solve the Navier-Stokes equations additionally, to evaluate the flexible deformation of fish in swimming accurately when satisfying the boundary conditions. A physical prototype to mimic the shape of tuna is developed with the revolutionized technology of rapid prototyping manufacturing. The hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The physical prototype of the fish-like model was developed as the shape of tuna with the revolutionary technology of rapid prototyping manufacturing, as reported in previous research (Xue, Liu, Zhang, & Ding, 2016). We used force sensors and signal acquisition modules to measure and record the transient hydrodynamic force with a sampling frequency of 0.1 s. The physical prototype could swim in a two-dimensional plane of a small water tank with the help of guide rails fixed on the support structure and the base support.…”
Section: Experimental Modelmentioning
confidence: 99%
“…The physical prototype of the fish-like model was developed as the shape of tuna with the revolutionary technology of rapid prototyping manufacturing, as reported in previous research (Xue, Liu, Zhang, & Ding, 2016). We used force sensors and signal acquisition modules to measure and record the transient hydrodynamic force with a sampling frequency of 0.1 s. The physical prototype could swim in a two-dimensional plane of a small water tank with the help of guide rails fixed on the support structure and the base support.…”
Section: Experimental Modelmentioning
confidence: 99%
“…Feilich and Lauder [ 22 ] indicated that the shape and stiffness can affect the hydrodynamic performance of a tuna-like tail. Xue et al [ 23 ] carried out a numerical hydrodynamic analysis for a physical prototype imitating the shape of tuna based on the Panel method. Then, Xue et al [ 24 ] discussed the evolvement rule and hydrodynamic effect of fluid field around tuna-like model from starting to cruising.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the application of bionics had attracted more and more attention of the researchers (Xue et al 2016;Hua et al 2019;Yang et al 2017;Gu et al 2019;Cheng et al 2020;Huang et al 2019). Some sinusoidal tubercles are growing in the pectoral fins of humpback, which allows them to move freely in the ocean.…”
Section: Introductionmentioning
confidence: 99%